(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Social isolation and economic catastrophic became the main characters of the current pandemic. Historically, the strongest stigmas related to diseases were characterized as highly transmittable, potentially lethal, and without remedy. All represented COVID-19 during the early transition into the new normal. We aimed to analyzed stigma and economic stressors concerning mental health. Method: We conducted a crosssectional online survey of 1375 participants in Java, Indonesia. Mental health status evaluated with DASS- 21. The presence of social and self-stigma related to Covid-19 assessed with a questionnaire developed based on seven domains of public stigma. Demographics and other psychosocial stressors were assessed with an online questionnaire. Descriptive analyses and logistic regression had carried out. Result: A very high percentage of perceived and anticipated self-stigma and social stigma revealed. Controlling demographics factors, clear self-stigma increased the risk for depression (2.323 (1.241-4.346), p<0.05), anxiety (2.134 (1.205-3.777), p<0.05) and stress 3.931 (1.779-8.685), P<0.001). Clear social stigma increased the risk for anxiety (2.000 (1.066-3.756), p<0.05) but not on depression and stress.Conclusion: Ensuring basic needs fulfilment and eliminating stigma is critical for supporting mental health in the Covid-19 pandemic. Further research into the stigma-related risks is necessary because it represents an important need for intervention in public health.